2019
DOI: 10.3390/ijms20235876
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impacts of the BRCA1-mTORC2 Interaction in Breast Cancer

Abstract: Deleterious mutations in Breast Cancer 1 (BRCA1) are associated with an increased risk of breast and ovarian cancer. Mutations in the tandem BRCA1 C-terminal (tBRCT) protein domain disrupt critical protein interactions required for the faithful repair of DNA through homologous recombination, which contributes to oncogenesis. Our studies have identified RICTOR, PRR5, and SIN1 subunits of the mammalian target of rapamycin complex 2 (mTORC2) as interacting partners with the tBRCT domain of BRCA1 leading to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Likewise, PARPi decrease PARP1-XPA associations and reduce chromatin binding of XPA, suggesting the close relationship of both BER and NER pathways [160]. There is emerging evidence of extensive interactions among proteins involved in distinct DNA repair pathways and it needs to be reflected when evaluating the cancer etiology, prognostic and predictive factors based on DNA repair and DDR [180,181]. Although the concerted action of various DNA repair pathways in tumorigenesis is postulated, there is however scarce experimental evidence on this interplay.…”
Section: Interplay Of Dna Repair Pathwaysmentioning
confidence: 99%
“…Likewise, PARPi decrease PARP1-XPA associations and reduce chromatin binding of XPA, suggesting the close relationship of both BER and NER pathways [160]. There is emerging evidence of extensive interactions among proteins involved in distinct DNA repair pathways and it needs to be reflected when evaluating the cancer etiology, prognostic and predictive factors based on DNA repair and DDR [180,181]. Although the concerted action of various DNA repair pathways in tumorigenesis is postulated, there is however scarce experimental evidence on this interplay.…”
Section: Interplay Of Dna Repair Pathwaysmentioning
confidence: 99%
“…Interestingly, mTOR has also been implicated in DNA replication stress [153]. In particular, the mTORC2 subunits Rictor, PRR5, and Sin1 have recently been shown to physically interact with the tBRCT domain of BRCA1, while the use of TOR inhibitors has suggested that mTORC2 and not mTORC1 is involved in activation of BRCA1-dependent transcription [154].…”
Section: Transcriptional Control By Torc2mentioning
confidence: 99%
“…It is worth noting that EC50 refers to the concentration of a drug, antibody or toxicant that achieves 50% of the maximum biological effect after a specified exposure time. It was commonly used as a measure of a drug's potency [ 31 ]. Kd is often used to describe degree of binding of a compound to a particular target [ 32 ].…”
Section: Resultsmentioning
confidence: 99%